The implementation of palliative care in Greece: a position paper by the Palliative Care Working Group of the Hellenic society of Medical Oncology (HeSMO) - Konstantis A.; Paraskeva M.; Avgoustidi M.; Kiagia M.; Kounnis V.; Rovithi M.; Alexaki M.; Ardavanis A.; Arvanitou E.; Tsoukalas N.; Agelaki S. (Forum of Clinical Oncology)
The global burden of cancer continues to rise, with projections indicating a 47% increase in new cases by 2040. The integration of oncology and palliative care has emerged as a vital approach to address the complex needs of cancer patients. This position paper, endorsed by the Palliative Care Working Group of the Hellenic Society of Medical Oncology (HeSMO), emphasizes the significance of early integration of palliative care with cancer-directed therapies. It highlights the benefits of this approach, including improved quality of life, symptom control, emotional well-being, and enhanced survival rates for patients. The paper also addresses the challenges of palliative care provision in Greece and advocates for comprehensive education for health-care professionals, especially oncologists and nurses, to effectively manage palliative care needs. The importance of multidisciplinary teams (MDTs), survivorship care plans (SCPs), home-based palliative care, and end-of-life care discussions is underscored. By aligning with international guidelines and recommendations, HeSMO strives to establish a supportive health-care system in Greece that offers equitable access to high-quality palliative care for all cancer patients, thus ensuring their well-being throughout their cancer journey.